(3eQBI GdYLGFHs - (3CHh YHO Gddg eMeO Hf GdegfGQs
(3ChdgG (B:s
(3GdMeO ddg GdPi JaQO HGdHbGA CeG HYO aGYdehG ENhGfi ai GdMbjbI CjOce Gddg hEjGi WdHJ Yde GdUfYI deG ajg ef GdLdGd hGdQaYI EP gi UfGYI ef CTQa GdUfGYGJ s
(3BNQgG (B:s
(3aGeRLg HUGO GdUaQI GdMGQI hGfKQ YdjgG ef GdbTQ GdJi hdjcf YfO JKdjK GdeTJQi hEjGc Cf JSJZQb aJaQb hGdSdGe aaQZJ ef bQGAI gPG GdcdGe hGfJHgJ ef GdefGe aeG COQi CMb Ce CVZGK CMdGe gPG BNQ GdQSGdI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1648s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WHjYI (B190) s
Keywords: (3GdcjejGA h GdWHjYjGJs